2016
DOI: 10.1088/2043-6262/7/4/045016
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient growth of vertically aligned carbon nanotubes on Fe–Ni based metal alloy foils for supercapacitors

Abstract: Supercapacitors are highly promising energy devices with superior charge storage performance and a long lifecycle. Construction of the supercapacitor cell, especially electrode fabrication, is critical to ensure good performance in applications. This work demonstrates direct growth of vertically aligned carbon nanotubes (CNTs) on Fe–Ni based metal alloy foils, namely SUS 310S, Inconel 600 and YEF 50, and their use in symmetric vertically aligned CNT supercapacitor electrodes. Alumina and cobalt thin film catal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…However, some studies concluded that the thermal conductivity depends on CNT directionality . Recently, several researchers have increasingly focused on vertically aligned CNT (VACNT) due to their high efficiency for heat transfer into ambient conditions . As shown in Figure , VACNT is successfully grown using plasma‐enhanced CVD (PE‐CVD) method, which commonly produces good‐quality CNT.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
See 3 more Smart Citations
“…However, some studies concluded that the thermal conductivity depends on CNT directionality . Recently, several researchers have increasingly focused on vertically aligned CNT (VACNT) due to their high efficiency for heat transfer into ambient conditions . As shown in Figure , VACNT is successfully grown using plasma‐enhanced CVD (PE‐CVD) method, which commonly produces good‐quality CNT.…”
Section: Carbon Allotrope Materials In Tims Applicationmentioning
confidence: 99%
“…24 Therefore, CNT is outstanding among advanced materials to be implemented in the thermal application and energy storage. CNTs are electrically conducting tools, which are comparable to diamond and have involved in many applications such as TIMs, [25][26][27] batteries, 28-30 energy storage, [31][32][33] supercapacitor, 34 fuel cell, [35][36][37][38] and portable sensors. [17][18][19]21,22 The synthesis of CNT is already established few years ago and has attained large scale of production.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
See 2 more Smart Citations
“…Modifying the synthesis conditions allows tuning of the geometry, alignment, density, and structure of CNTs, which offers control over their mechanical performance [5,6,7,8,9,10]. CNT forests grown directly on metal substrates, and specifically on steels, are particularly interesting because they offer a conformal coating solution, which is independent from the substrate’s geometry [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. Direct growth avoids the need for intermediate adhesive layers, thus enabling a robust contact interface between the CNTs and the metal [12].…”
Section: Introductionmentioning
confidence: 99%